2012
DOI: 10.1042/bj20120768
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferase 5 is essential for growth of lung cancer cells

Abstract: Protein arginine methyltransferase 5 (PRMT5) is an enzyme that catalyzes transfer of methyl groups from S-adenosyl methionine to the arginine residues of histones or nonhistone proteins and is involved in a variety of cellular processes. Although it is highly expressed in some tumors, its direct role in cancer growth has not been fully investigated. In this study, in human lung tissue samples, we found that PRMT5 was highly expressed in lung cancer cells whereas its expression was not detectable in benign lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
120
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 43 publications
(59 reference statements)
6
120
0
Order By: Relevance
“…Ullman and colleagues reported that PRMT5 accelerates tumor growth by arginine methylation of tumor suppressor programmed cell death 4 (31). Gu et al (32) suggested that PRMT5 is essential for the growth of lung cancer cells. Wei et al (33) reported that PRMT5 is a potential oncoprotein that up-regulates G1 cyclins and cyclindependent kinases and the phosphoinositide 3-kinase/AKT signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Ullman and colleagues reported that PRMT5 accelerates tumor growth by arginine methylation of tumor suppressor programmed cell death 4 (31). Gu et al (32) suggested that PRMT5 is essential for the growth of lung cancer cells. Wei et al (33) reported that PRMT5 is a potential oncoprotein that up-regulates G1 cyclins and cyclindependent kinases and the phosphoinositide 3-kinase/AKT signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Although recurrent mutations of PRMT5 have not been observed in cancer cells, PRMT5 expression is upregulated in human leukemia, lymphoma, and in many solid tumors, including gastric, colorectal, and lung cancer tumors (15). PRMT5 promotes the proliferation of lung and ovarian cancer cells, rendering it an attractive therapeutic target in these diseases (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…1D). Since PRMT5 expression is also required for the growth of lung cancer cells (A549) [3], we transfected these reporter genes into A549 cells and observed that the reporter gene activity of B5 in A549 was 2-fold higher than that in LNCaP and PC-3 cells, though a comparable reporter gene activity of B6 and B7 was observed in all three cell lines (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PRMT5 may function as an oncogene to promote cancer cell growth [13, 57, 9, 10]. Although NF-Y directly regulates transcription of many target genes to control cell cycle progression, cell proliferation and cell survival [12, 13, 15, 17], our finding that NF-Y transcriptionally activates PRMT5 expression suggests that NF-Y may also regulate cancer cell growth by controlling the expression level of PRMT5, an emerging epigenetic enzyme that functions as an oncogene in human cancers [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation